ANALISIS KESALAHAN BERBAHASA PADA TATARAN FRASA DALAM PUTUSAN PENGADILAN KASUS TINDAK PIDANA KEJAHATAN TERHADAP NYAWA - Sulistyowati, Ririn (MIMESIS, 2023)
Court order are a scientific product of the legal process, so there should be no mistakes in writing court order because this can have fatal consequences for the legal process that has been carried out. Phrases as the smallest level in the syntax used to form sentences must be written correctly in a court order to avoid misinterpretation of a court order. This study will describe the various language errors at the phrase level that can be found in court order on homicide act of criminal. This research is a qualitative descriptive study. The data in this study are sentences containing language errors at the phrase level contained in a court order of homicide act of criminal in North Sumatra in 2020.  The conclusions in this study are made inductively. Based on the analysis in this study, it can be concluded that there are six types of language errors, namely the influence of regional languages, inappropriate use of prepositions, wording errors, excessive use of elements, errors in the use of superlative forms, and pluralization of plural forms.